Trigger Point Injections for Headache Disorders: Expert Consensus Methodology and Narrative Review. Issue 9 (28th August 2014) - Robbins, Matthew S.; Kuruvilla, Deena; Blumenfeld, Andrew; Charleston, Larry; Sorrell, Michael; Robertson, Carrie E.; Grosberg, Brian M.; Bender, Steven D.; Napchan, Uri; Ashkenazi, Avi
Abstract : Objective/Background: To review the existing literature and describe a standardized methodology by expert consensus for the performance of trigger point injections (TPIs) in the treatment of headache disorders. Despite their widespread use, the efficacy, safety, and methodology of TPIs have not been reviewed specifically for headache disorders by expert consensus. Methods: The Peripheral Nerve Blocks and Other Interventional Procedures Special Interest Section of the American Headache Society over a series of meetings reached a consensus for nomenclature, indications, contraindications, precautions, procedural details, outcomes, and adverse effects for the use of TPIs for headache disorders. A subcommittee of the Section also reviewed the literature. Results: Indications for TPIs may include many types of episodic and chronic primary and secondary headache disorders, with the presence of active trigger points (TPs) on physical examination. Contraindications may include infection, a local open skull defect, or an anesthetic allergy, and precautions are necessary in the setting of anticoagulant use, pregnancy, and obesity with unclear anatomical landmarks. The most common muscles selected for TPIs include the trapezius, sternocleidomastoid, and temporalis, with bupivacaine and lidocaine the agents used most frequently. Adverse effects are typically mild with careful patient and procedural selection, though pneumothorax and other serious adverse events have been infrequently reported. Conclusions: When performed in the appropriate setting and with the proper expertise, TPIs seem to have a role in the adjunctive treatment of the most common headache disorders. We hope our effort to characterize the methodology of TPIs by expert opinion in the context of published data motivates the performance of evidence‐based and standardized treatment protocols.